FABRIKASI DAN ANALISIS PROSES MANUFAKTUR CAVITY BLADE TURBIN MODEL GORLOV SEBAGAI CETAKAN FIBERGLASS DENGAN METODE HAND LAY UP (HLU) - Afishiena Afishiena; George Endri Kusuma; Pranowo Sidi (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Electrical energy is an important source of energy for the people of Indonesia because electrical energy is always used in industrial activities and daily life. Indonesia's power generation capacity has increased by almost 15 Giga Watt (GW) to 69.6 Giga Watt (GW) from 54.7 to 69.6 Giga Watt (GW) in the Turbine last five years. This need will continue to grow because fossil raw materials will gradually be eroded. One of the efforts to utilize energy is the renewable energy of the Picohydro Power Plant which utilizes the flow of the river or sea currents as renewable energy. This research is to design a Gorlov Model Blade mold with fiberglass using the Hand Lay Up method. In the process using the Reverse Engineering method to compare the 3 Manufacturing Processes for making the Gorlov model turbine blade mold. In this study, the first process concept was chosen because the price is cheaper, the process is easy and fast, and has a lighter weight than the existing product. The results of the Gorlov Model Blade Turbine performance test on a river flow with an average speed of 1.59 m/s and a river depth of 300 mm resulted in Blade 732.28 Rpm and produced 3.2 Volts. From these data, it can be said that the turbine can work according to its function. Total Cost of Production (HPP) Rp. 5.570.350.